Characteristics and effectiveness of interventions to reduce cyberbullying: a systematic review - Henares-Montiel, Jesús; Pastor-Moreno, Guadalupe; Ramírez-Saiz, Alberto; Rodríguez-Gómez, Marina; Ruiz-Pérez, Isabel (Frontiers in Public Health, 2023)
Background: This paper presents the results from a systematic review on the effectiveness of interventions to reduce Cyberbullying (CB) as a function of their outcomes and main characteristics; and an analysis of the level of completeness to which the characteristics of these interventions are described.Methods: Systematic searches were conducted in PubMed, Scopus, ERIC and Psycinfo databases on February 14, 2022. In addition, relevant publications were hand searched for relevant studies. We considered interventions that provided data on CB prevalence changes in populations between primary school and college age.In total, 111 studies were retained for further screening from 3477 results. Following rigorous screening, 43 reports including 46 studies and information from 36 different interventions were included in our systematic review. Results shows that most of the interventions measuring reductions in global CB, cyberperpetration/victimization, cybervictimization and cyberperpetration were effective or partially effective. While the interventions measuring reductions in cyberbystanding were not effective. Multicomponent interventions showed higher effectiveness than single-component interventions. After completion of the TIDieR check-list, included interventions were considered to offer an insufficient level of detail for a number of the analyzed items in relation to "how well planned", "intervention modifications" and "tailoring".Given the aforementioned, it is critical to increase the number of studies and the quality of interventions targeting CB and the level of detail of its description in order to obtain more robust outcomes about how to reduce its prevalence and facilitate the replication of the effective interventions.